Carbon Capture - Abdul Rehman Khan, Syed (IntechOpen, 2021)
This book differs from others on the subject of pollution and carbon emissions by focusing on environmental issues at domestic levels. It presents important information on the far-ranging effects of greenhouse gases on the environment and examines potential solutions to controlling carbon emissions.